Pengaruh Pengelolaan Modal Kerja Terhadap Kinerja Perusahaan Jasa Konstruksi PT Waskita Karya (Persero) Tbk - Rudy H. S. Pardede; Hermanto Siregar; Trias Andati (Politeknik Ganesha Medan, 2025)
This research examines the influence of working capital management on the performance of PT Waskita Karya (Persero) Tbk. (WSKT), one of the largest construction services companies in Indonesia which has been involved in toll road investment since 2015. An increase in debt that is not proportional to income as well as negative cash flow and a decrease in equity indicate pressure in managing costs and income. This research analyzes the relationship between working capital policy, working capital management, and company performance as measured by Return on Assets (ROA), Return on Equity (ROE), and Tobin's Q. Data are taken from quarterly financial reports for the period 2013 to quarter 1 of 2024 . The research method involves multiple linear regression analysis and evaluation of variables such as Average Collection Period (ACP), Average Payment Period (APP), Inventory Conversion Period (ICP), and Cash Conversion Cycle (CCC). The results show that working capital management has a significant effect on company performance. ACP, APP, ICP, and CCC significantly influence ROA, ROE, and Tobin's Q. Aggressive investment policy (AIP) and aggressive financing policy (AFP) were also found to influence performance, with the implication that effective working capital management is the key to improving construction company performance.